Ordens militares e fronteira : um desempenho militar, jurisdicional e político em tempos medievais - Costa, Paula Pinto (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The application of the crusade to the Iberian territory gives way to the cooperation between the Military Orders and the monarchy in enlarging the territory and creates a convergence of interests in favour of these institutions, whose effects will extend beyond the reconquering period (Reconquista). In this sense, there is an evolution in the performance of the Military Orders since their participation in defining the territorial frontier (12th-13th centuries) to the construction of the frontier characterised by the strategic projection (14th-15th centuries), structured in two orienting vectors: North-English Channel (Santiago and Avis) and South-Mediterranean and Atlantic (Hospital and Christ).